BlockchainBus: A lightweight framework for secure virtual machine migration in cloud federations using blockchain. Issue 2 (30th November 2021) - Doyle, Joseph; Golec, Muhammed; Gill, Sukhpal Singh
Abstract: Cloud federations offer numerous advantages such as improved resilience, improved performance, and the prevention of vendor lock‐in. In order to function efficiently, however, they must be supported by automated solutions to deploy cloud resources securely and efficiently. In particular, a system which allows virtual machine (VM) migration from one cloud to another while recording this for charging and security purposes is particularly useful. This paper presents a lightweight framework called BlockchainBus which offers secure VM migration in cloud federations using blockchain. This framework is a VM migration Blockchain ledger which can be used to record these migrations. BlockchainBus framework is implemented using the HyperLedger solution and deployed on the Microsoft Azure cloud platform. The overhead of this system is then evaluated. The performance of the BlockchainBus framework was compared with the overall VM migration time and was determined as 2.36 seconds. This result is shorter than the overall VM migration time of 5 seconds and indicates that the BlockchainBus gives better performance.